ANALISIS PRODUKSI INDUSTRI FURNITURE DARI KAYU DI KOTA PEKANBARU - Riski Maryati; Azwar Harahap; Taryono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in the city of Pekanbaru. This study aims to determine how the effect of variable raw materials, auxiliary materials, labor and capital to the industrial production of wood furniture in the city of Pekanbaru and determine the efficiency of use of raw materials, auxiliary materials, labor and capital as well as to determine the scale of production (Return to Scale). This study uses census, for the respondents are all business actors of the wood furniture industry in Pekanbaru City numbering 36 business units . The method of analysis in this Penalitian is descriptive quantitative analysis of Cobb-Douglas production function, partial and simultaneous analysis by means of linear regression. Results of the study showed that partially (t test), there are three variables, namely raw materials, auxiliary materials and labor which has significant influence on the dependent variable, while one other variable that capital has no significant effect on the dependent variable. Simultaneously (Test f) four independent variables have a significant influence. Value of labor input price efficiency of 4156.44 or more than 1. For it is necessary to increase the amount of labor. While the three other production input efficiency values obtained input prices that are less than 1 is equal to 0.399 for raw material input prices, input prices -0.927 to 0.024 auxiliary materials and capital for input prices. It is necessary for the proper proportions in the use of production inputs such third. Decreasing returns to scale production show Return To Scale because β1 + β2 + β3 + β4 <1. This means that in case of additional factors of production by 1 percent, then the production will increase by 0.973 smaller than the addition of input. This is because the use of factors of production is not maximized.Keywords: Production, Raw Materials, Materials Assistant, Labour, and Capital